Secular trends in the prevalence of abdominal obesity among Chinese adults with normal weight, 1993–2015 - Xingxing Sun (Nature Portfolio, 2021)
Abstract A considerable chronic disease burden existed in people with normal body mass index (BMI), it is imperative to study the prevailing trends in abdominal obesity among Chinese people with normal BMI. Hence, we aimed to analyze updated prevalence data on abdominal obesity trends among Chinese adults with a normal BMI. We used data from the China Health and Nutrition Survey (CHNS) conducted between 1993 and 2015. Abdominal obesity is defined as waist circumference (WC) ≥ 90 cm for men and ≥ 80 cm for women following the International Diabetes Federation recommendations for Asians. Over the 23-year period, the age-standardized mean WC values showed a significant increasing trend among Chinese adults with BMI < 25 kg/m2, with the mean value increased from 74.0 cm to 78.5 cm (P for trend < 0.0001). During the period of 1993–2015, the age-standardized prevalence of abdominal obesity increased from 12.1 to 26.0% (P for trend < 0.0001). Significant increases were observed in both sexes, all age groups, rural and urban residents, and all educational attainment groups (all P for trends < 0.0001), with a greater relative increase noted among men, younger participants, and rural residents. Similar significant trends were noted when a more stringent BMI < 23 kg/m2 cut point (Asian cut point) was applied. A low magnitude of overlap existed between abdominal obesity and general obesity, irrespective of the criteria used. The mean WC and the prevalence of abdominal obesity among Chinese adults with normal BMI increased continuously from 1993 to 2015. The upward trends were noted in both sexes, all age groups, rural and urban regions, and all educational attainment groups. Our estimates emphasize the importance of adding WC in addition to BMI as measures to monitor obesity prevalence.